Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus Pada Perusahaan JNE Cabang Lhokseumwe) - Khairina AR; Nada Julianda (Jurnal Visioner & Strategis, 2020)
This study aims to determine the effect of Service Quality on Customer Satisfaction (a Case Study at JNE Company of Lhokseumawe City Branch). It is a quantitative descriptive study, and the population is all customers or consumers who use the JNE courier service in the Lhokseumawe City Branch, which is unlimited (infinite). The type of non-probability sampling used by researchers in this study is Accidental sampling. This study uses primary and secondary data obtained by distributing questionnaires to 100 respondents who were selected using a sample research technique based on chance, namely selecting respondents by visiting respondents and then selecting prospective respondents who are met by chance. The data analysis method used is a multiple linear regression method with the help of SPSS. The results show that physical evidence has a positive and significant effect on customer satisfaction at JNE companies, reliability has a positive and insignificant effect on customer satisfaction at JNE companies, responsiveness has a positive and significant effect on customer satisfaction at JNE companies, and assurance has a positive and insignificant effect on customer satisfaction. Customer satisfaction at JNE companies and empathy has a positive and significant effect on customer satisfaction at JNE companies.Keywords: Service Quality, Customer Satisfaction